DIAGNOSIS OF INFECTIOUS NECROTIC HEPATITIS DISEASE - Salimov Ilkhom Khaitovich; Hakimov Shorasul (Journal of Medical Genetics and Clinical Biology, 2024)
The article outlines laboratory techniques for diagnosing infectious necrotic hepatitis in sheep using pathological material. It also provides guidance on how to properly choose, package, and transmit the pathological material from deceased sheep to the laboratory. The process of isolating the causative agent of the disease and examining its cultural, morphological, and biological features. Additionally, a biological research method for studying this infection is also available